Beyond influence: Contextualization and optimization for new narrative techniques and story-formats. Perspective paper - Petrovic, Milica; Liedgren, Johan; Gaggioli, Andrea (Frontiers in Communication, 2022)
In a society where advances and innovations occur on a daily basis, outreach and meaningful engagement with the general public become more challenging. The amount of information produced and repackaged surpasses existing systems in place to ensure truthful and factual engagement with the public, especially with complex matters regarding health science. This perspective paper discusses the value of contextualization and optimization for creating transparent and engaging content. We reflect on the innovative Transformative Storytelling Technique as a new category creating hybrid content to guide the experience of audiences, starting with the case of informal caregivers helping individuals living with neurological conditions. Moreover, we share our perspective on the important considerations for current and future development of highly targeted content using this technique. We include reflexions around the risks and ethical principles needed in the utilization and dissemination of “guided” content for the general public.